EDITORIAL: Celebrating a Milestone: Journal Impact Factor Achievement and the Future of the IJIEM - Marjanovic, Ugljesa (International Journal of Industrial Engineering and Management, 2013)
It is with great pleasure and excitement that I share with you a momentous achievement for the International Journal of Industrial Engineering and Management (IJIEM). We have recently received our inaugural Journal Impact Factor (JIF), a significant milestone that reflects the growing recognition and influence of our journal within the category engineering, industrial. The JIF serves as a quantitative measure of a journal’s importance and reach within the academic community. It represents the average number of citations received by articles published in the journal over a specific period. Achieving this milestone signifies that the scholarly work published in our journal is making a meaningful impact and contributing to the advancement of industrial engineering and production management knowledge.